Gastric antral vascular ectasia: maintenance treatment with oestrogen-progesterone. Issue 5 (May 1992) - Moss, S F; Ghosh, P; Thomas, D M; Jackson, J E; Calam, J
Abstract : Gastric antral vascular ectasia ('watermelon stomach') is a rare cause of chronic gastrointestinal bleeding and various medical and surgical treatments have been described. We report a patient in whom an oestrogen-progesterone preparation successfully controlled recurrent blood loss.